Dust exposure and pneumoconiosis in a South African pottery. 1. Study objectives and dust exposure. Issue 7 (July 1992) - Rees, D; Cronje, R; du Toit, R S
Abstract : Dust exposure and pneumoconiosis were investigated in a South African pottery that manufactured wall tiles and bathroom fittings. This paper describes the objectives of the investigation and presents dust measurement data. x Ray diffraction showed that the clays used by the pottery had a high quartz content (range 58%-23%, mean 38%). Exposure to respirable dust was measured for 43 workers and was highest (6.6 mg/m3) in a bathroom fitting fettler. Quartz concentrations in excess of 0.1 mg/m3 were found in all sections of the manufacturing process from slip production to biscuit firing and sorting. The proportion of quartz in the respirable dust of these sections was 24% to 33%. This is higher than is usually reported in English potteries. Four hundred and six (80%) of the 509 workers employed at the pottery were potentially at risk of occupational lung disease. The finding of large numbers of pottery workers exposed to unacceptable dust concentrations is not surprising as poor dust control was found in all six wall tile and sanitary ware factories surveyed by the National Centre for Occupational Health between 1973 and 1989. Dust related occupational disease can be expected in potters for many years to come.